ANALISIS MAKNA PADA PEPACCUR ADEK ANJAK LEBEU DALAM BUKU SASTRA LISAN LAMPUNG DIALEK PUBIAN - Fauzi , Irfan; Budiman , Ahmad Arif; Prayogi , Rahmat; Riadi , Bambang (Jurnal Tiyuh Lampung: Pendidikan Bahasa dan Kebudayaan, 2024)
This research describes the analysis of the meaning of Pepaccur Adek Anjak Lebeu in the book Lampung Oral Literature Pubian Dialect. The problem formulation was found about "How is the analysis of the meaning of Pepaccur Adek Anjak Lebeu in the book of Lampung Oral Literature in Pubian Dialect". The purpose of this research is to deepen the analysis of the meaning of Pepaccur Adek Anjak Lebeu in the book Lampung Oral Literature Pubian Dialect. Lampung pepaccur oral literature is a traditional form of poetry or narrative often used in traditional ceremonies and important gatherings to convey advice, history, and cultural values. The meaning of the pepaccur reflects moral messages and life advice passed down from generation to generation. In this pepaccur, the importance of knowing one's origins and family pride is emphasized as the basis for building a strong self-identity. This message reminds descendants not to hesitate in recognizing and appreciating the heritage of their ancestors. The advice given is also very relevant to everyday life. Children and grandchildren are reminded to work diligently and with discipline, and to make the most of their time. This is a warning not to waste opportunities, given the rapid development of science and technology in this day and age. Those who are careless and do not try hard will be left behind and regret it later on. Overall, the pepaccur conveys the importance of work ethic, discipline, and respect for time and cultural heritage. Penelitian ini menjelaskan tentang analisis makna Pepaccur Adek Anjak Lebeu dalam buku Sastra Lisan Lampung Dialek Pubian. Ditemukan rumusan masalah tentang “Bagaimana analisis makna Pepaccur Adek Anjak Lebeu dalam buku Sastra Lisan Lampung Dialek Pubian”. Tujuan penelitian ini untuk memperdalam analisis makna Pepaccur Adek Anjak Lebeu dalam buku Sastra Lisan Lampung Dialek Pubian. Sastra lisan pepaccur Lampung adalah bentuk tradisional puisi atau narasi yang sering digunakan dalam upacara adat dan pertemuan penting untuk menyampaikan nasihat, sejarah, dan nilai-nilai budaya. Makna dari pepaccur ini mencerminkan pesan moral dan nasihat kehidupan yang diturunkan dari generasi ke generasi. Dalam pepaccur ini, ditekankan pentingnya mengenal asal-usul dan kebanggaan keluarga sebagai dasar untuk membangun identitas diri yang kuat. Pesan ini mengingatkan keturunan untuk tidak ragu dalam mengenali dan menghargai warisan nenek moyang mereka. Nasihat yang diberikan juga sangat relevan untuk kehidupan sehari-hari. Anak cucu diingatkan untuk bekerja dengan tekun dan disiplin, serta memanfaatkan waktu sebaik mungkin. Ini adalah peringatan untuk tidak menyia-nyiakan kesempatan, mengingat perkembangan ilmu dan teknologi yang pesat di zaman sekarang. Mereka yang lengah dan tidak berusaha keras akan tertinggal dan menyesal di kemudian hari. Secara keseluruhan, pepaccur ini menyampaikan pentingnya etos kerja, disiplin, dan penghargaan terhadap waktu serta warisan budaya. Ini adalah pelajaran berharga bagi generasi muda untuk menghadapi tantangan masa kini dengan fondasi yang kuat dari nilai-nilai tradisional.